Multimode Silicon Nanowire Transistors - Glassner, Sebastian; Zeiner, Clemens; Periwal, Priyanka; Baron, Thierry; Bertagnolli, Emmerich; Lugstein, Alois (Nano letters, 2014)
The combined capabilities of both a nonplanar design and nonconventional carrier injection mechanisms are subject to recent scientific investigations to overcome the limitations of silicon metal oxide semiconductor field effect transistors. In this Letter, we present a multimode field effect transistors device using silicon nanowires that feature an axial n-type/intrinsic doping junction. A heterostructural device design is achieved by employing a self-aligned nickel-silicide source contact. The polymorph operation of the dual-gate device enabling the configuration of one p- and two n-type transistor modes is demonstrated. Not only the type but also the carrier injection mode can be altered by appropriate biasing of the two gate terminals or by inverting the drain bias. With a combined band-to-band and Schottky tunneling mechanism, in p-type mode a subthreshold swing as low as 143 mV/dec and an ON/OFF ratio of up to 104 is found. As the device operates in forward bias, a nonconventional tunneling transistor is realized, enabling an effective suppression of ambipolarity. Depending on the drain bias, two different n-type modes are distinguishable. The carrier injection is dominated by thermionic emission in forward bias with a maximum ON/OFF ratio of up to 107 whereas in reverse bias a Schottky tunneling mechanism dominates the carrier transport.